Acceptance and commitment therapy in a psychiatric day hospital—A longitudinal naturalistic effectiveness trial - Rutschmann, Ronja; Romanczuk-Seiferth, Nina; Richter, Christoph (Frontiers in Psychiatry, 2023)
Despite the transdiagnostic approach and the good cross-professional applicability, only few studies have examined the effects of Acceptance and Commitment Therapy (ACT) in a naturalistic clinic setting. This study aims to help closing this gap by investigating the effects of ACT in a transdiagnostic day hospital during COVID pandemic. It was investigated whether psychopathological symptomology decreased, and quality of life and general functioning improved with the treatment. Additionally, longitudinal effects were tested. Participants in this follow-up-design were 92 patients (64.1% female) of an acute day hospital. Survey data of clinical symptoms, quality of life and global functioning were assessed at three time points (with admission, discharge, and three months after treatment). Differences between time points were tested using two-sided paired samples t-tests. Additionally, the reliability of change index (RCI) was calculated. From pre-treatment to post-treatment, symptomology decreased significantly (d = 0.82-0.99, p < .001), and global functioning as well as quality of life increased significantly (d = 0.42-1.19, p < .001). The effects remained relatively stable, with no significant change between post-treatment and follow-up. The difference between pre-treatment and follow-up was significant for clinical symptoms, physical and psychological well-being, and global quality of life (d = 0.43-0.76, p < .007). The significant and sustained improvement in all measures indicates that patients are benefiting from the treatment. Since the trial was neither randomized nor controlled, effects have to be interpreted with caution. Possible influences of the pandemic are discussed. The study was retrospectively registered in the German Clinical Trials Register (DRKS-ID: DRKS00029992) on August 19th, 2022.